Performance Enhancements in IEEE 802.11 DCF MANET through Variation of SIFS Values in Distance Vector Routing Environment - Md Khambari, M. N.; Muhamad Noh, Z. A.; Mat Ariff, N. A.; Mas'ud, M. Z. (2011)
This paper describes and investigates the performance enhancement techniques used in IEEE 802.11g MANET in AODV and DSDV routing environment. Through variation of Short Interframe Space (SIFS) values, a better scheme to enhance the wireless network performance can be achieved. This is important especially to assign high priority network nodes that carry time sensitive data to reach the intended receiver in a timely manner. Using NS-2, network simulations are done and the findings are presented. It is showed that nodes using the variated SIFS values can achieve higher throughput compared to nodes using the default SIFS values.